Comparative economic evaluation of rosemary (Rosmarinus officinalis L.) and wheat (Triticum aestivum L.) cultivation in Ethiopia - Geyo, Guta B. (Frontiers in Environmental Economics, 2025)
Spices and aromatic plants have been used for flavoring, coloring, enhancing aromas, and preserving food. In addition, spice products, essential oils, and oleoresin processors are expanding; hence, the demand for spices and aromatic and medicinal plants is increasing. This study aimed to analyze the economic performance of rosemary production and processing compared to wheat production in the selected areas. The study evaluated wheat production and its benefit–cost ratio to compare it with rosemary production. The average revenue obtained from wheat sales was 34,024 birr, with an average cost of 15,173, resulting in a net revenue of 18,851 birr for the farmland condition. Rosemary production and the benefit–cost ratio were evaluated at the farm level. The average revenue obtained from rosemary sales was 73,454 birr, with an average cost of 35,868, resulting in a net revenue of 37,585 birr for the farmland condition. The coverage area for rosemary was 0.14 ha, which was smaller than the coverage area for wheat. Even with the smaller area allocated for rosemary, it was found that a net revenue of 37,585 birr was obtained from rosemary sales compared to a net revenue of 18,851 birr from wheat sales in the farm condition.